2013
DOI: 10.1007/s10865-013-9546-1
|View full text |Cite
|
Sign up to set email alerts
|

The presence of a dog attenuates cortisol and heart rate in the Trier Social Stress Test compared to human friends

Abstract: Limited research has addressed how social support in the form of a pet can affect both sympathetic and hypothalamic-pituitary-adrenal reactivity in response to a psychological challenge. The present study examined the effects of social support on salivary cortisol and heart rate (HR). Forty-eight participants were randomly assigned to three different conditions (human friend, novel dog, or control). All participants completed the Trier Social Stress Test and provided cortisol, HR, and State-Trait Anxiety Inven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(118 citation statements)
references
References 45 publications
6
111
0
1
Order By: Relevance
“…A study by Cole et al [31] found that patients hospitalized with advanced heart failure who received a visit from a therapy dog had lower cardiopulmonary pressures, neurohormone levels and state anxiety levels compared to patients who received a visit from a volunteer without a dog and the control group, however despite these changes in cardiopulmonary pressures, there were no significant differences found in heart rate, blood pressure, cardiac index and systemic vascular resistance. [31] These findings vary from those of Friedmann et al [24], Allen et al [25], and Polheber & Matchock [26] who found reductions in blood pressure [24] [25] [47] and heart rate [25] [26] in otherwise healthy populations when interacting with a dog.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A study by Cole et al [31] found that patients hospitalized with advanced heart failure who received a visit from a therapy dog had lower cardiopulmonary pressures, neurohormone levels and state anxiety levels compared to patients who received a visit from a volunteer without a dog and the control group, however despite these changes in cardiopulmonary pressures, there were no significant differences found in heart rate, blood pressure, cardiac index and systemic vascular resistance. [31] These findings vary from those of Friedmann et al [24], Allen et al [25], and Polheber & Matchock [26] who found reductions in blood pressure [24] [25] [47] and heart rate [25] [26] in otherwise healthy populations when interacting with a dog.…”
Section: Discussionmentioning
confidence: 90%
“…In a similar study by Polheber & Matchock [26] examining 85 undergraduate students, heart rate, anxiety and cortisol levels were recorded during a social stressor by comparing three conditions: a novel dog in a laboratory condition, a supportive friend and no social support. The researchers found that non-human social support in the form of a dog served to attenuate salivary cortisol levels and heart rate when compared to the friend (human social support) and control (no social support) conditions [26].…”
Section: Introduction and Review Of Literaturementioning
confidence: 99%
“…Conclusions of this study suggested that even when the perceived relationship quality is similar for pet dogs and close friends, dogs may provide more cardiovascular benefits during and after a stressful event (Campo and Uchino 2013). As one final example, a study by Polheber and Matchock (2014) found that the presence of a novel dog during a socially stressing event can positively impact participants' heart rate and cortisol response. Similar to results reported by Campo (2013), this study found that the presence of the dog reduced salivary cortisol levels even more than when participants were accompanied by a friend or alone (Polheber and Matchock 2014).…”
Section: Physical Healthmentioning
confidence: 99%
“…Increase in oxytocin level is important in human health, as oxytocin may be a mechanism for the stress-buffering effects of social support (Heinrichs et al 2003). There is also evidence for HAI decreasing the stress hormone cortisol even in short-term exposure to a dog (Polheber and Matchock 2014).…”
Section: The Basis For Psychological Wellnessmentioning
confidence: 99%